1988
DOI: 10.1099/00221287-134-9-2605
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase Activity in Rumen Ciliate Protozoa

Abstract: 2605Azocasein-degrading proteinase activity was detected in all rumen ciliate protozoa that were examined from four entodiniomorphid and two holotrich genera. All of the activities were optimal in the range pH 4.0-5.0 and were inhibited by cysteine proteinase inhibitors, notably leupeptin. The inhibition profiles and extent of inhibition observed with the different groups of inhibitors were organism-specific. Gelatin-SDS-polyacrylamide gel electrophoresis of protozoal lysates revealed multiple forms of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Moreover, incubations with mannose (Lockwood et al ., 1988) or wide spectrum antibiotics (Heald et al ., 1952) have also been described as effective procedures to lyse holotrich- or protozoal-associated bacteria, respectively. Nonetheless, in preliminary studies, we observed that these compounds could alter the methanogen population and therefore were not used here.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, incubations with mannose (Lockwood et al ., 1988) or wide spectrum antibiotics (Heald et al ., 1952) have also been described as effective procedures to lyse holotrich- or protozoal-associated bacteria, respectively. Nonetheless, in preliminary studies, we observed that these compounds could alter the methanogen population and therefore were not used here.…”
Section: Discussionmentioning
confidence: 99%
“…The connection between protozoa and CH 4 is known, because methanogenic archaea are known to attach to the surface of protozoa, and furthermore appear to live in the cytoplasm of the protozoa as intracellular commensal or symbiotic organisms (Finlay et al 1994). Protozoa are proteolytic (Lockwood et al 1988), which may explain the second connection. However, the relationship between protozoa and acidosis is usually thought to involve the protozoa protecting against acidosis by engulfing starch so that it is not susceptible to bacterial attack (Williams & Coleman, 1992), not the protozoa causing acidosis that seems to be the case in this situation.…”
Section: 'Rumen-up'mentioning
confidence: 99%
“…Lockwood et al 4 ) have shown that the proteolytic activity of Entodiniinae were greater than that of Isotrichids. Furthermore, in these experiments, the proportion of Entodiniinae was more than 98 % of the mixed rumen protozoa.…”
Section: Discussionmentioning
confidence: 99%